Crystallization and preliminary x-ray diffraction analysis of beta-cinnamomin, an elicitin secreted by the phytopathogenic fungus Phytophthora cinnamomin. - Archer, M; RODRIGUES, M L; Aurélio, M; Biemans, R; Cravador, A; Carrondo, M a (Acta crystallographica. Section D, Biological crystallography, 2000)
Cinnamomin (CIN) belongs to a family of 10 kDa proteins designated as elicitins. Some of these proteins induce a hypersensitive response in diverse plant species, leading to resistance against fungal and bacterial plant pathogens. CIN was crystallized by the vapour-diffusion method using either ammonium sulfate or polyethyleneglycol (PEG) as precipitants in solutions buffered at around pH 7. These crystals are isomorphous and belong to the triclinic space group, with unit-cell parameters a = 31.69, b = 36. 99, c = 44.09 A, alpha = 76.86, beta = 84.41, gamma = 80.26 degrees. A frozen crystal diffracted X-rays beyond 1.45 A resolution on a synchrotron-radiation source.
Keywords: Beta-cinnamomin; Elicitins; Phytopathogenic fungi